The mobile phone in governance for environmental sustainability in Sub-Saharan Africa - Simplice Asongu; Rexon T. Nting (African Governance and Development Institute (AGDI), 2021)
In this study, we assess how the mobile phone can be leveraged upon to improve the role of governance in environmental sustainability in 44 Sub-Saharan African countries. The Generalised Method of Moments is used to establish policy thresholds. A threshold is a critical mass or level of mobile phone penetration at which the net effect of governance on Carbon dioxide (CO2) emissions changes from positive to negative. Mobile phone penetration thresholds associated with negative conditional effects are: 36 (per 100 people) for political stability/no violence; 130 (per 100 people) for regulation quality; 146.66 (per 100 people) for government effectiveness; 65 (per 100 people) for corruption-control and 130 (per 100 people) for the rule of law. Practical and theoretical implications are discussed. The study provides thresholds of mobile phone penetration that are critical in complementing governance dynamics to reduce CO2 emissions.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; ICT; Economic development; Africa